A novel synthetic route to highly cross-linked poly(vinyl ethers) .3. Synthesis and free radical polymerization of aryloxyethyl vinyl ethers having an electron acceptor in ortho- or meta-position - Lee, JY; Kim, MY; Ahn, KD (KOREAN CHEMICAL SOC, 1997)
o-(2-vinyloxyethoxy)benzylidenemalononitrile (3a) and methyl o-(2-vinyloxyethoxy)-benzylidenecyanoacetate (3b), m-(2-vinyloxyethoxy)benzylidenemalononitrile (4a), and methyl m-(2-vinyloxyethoxy)benzylidenecyanoacetate (4b) were prepared by the condensation of o-(2-vinyloxyethoxy)benzaldehyde (1) and m-(2-vinyloxyethoxy)benzaldehyde (2) with malononitrile or methyl cyanoacetate, respectively. Bifunctional vinyl ether monomers 3a and 3b polymerized quantitatively with radical initiators in gamma-butyrolactone solution at 65 degrees C, while meta-isomers 4a and 4b gave lower yields of polymers under the same conditions. The polymers 5-6 obtained from the monomers 3-4 were insoluble in common solvents due to cross-linking. Under the same polymerization conditions ethyl vinyl ether polymerized well with model compounds o-methoxybenzylidenemalononitrile 7a, methyl o-methoxybenzylidenecyanoacetate 7b, m-methoxybenzylidenemalononitrile 8a, and methyl m-methoxybenzylidenecyano acetate 8b, respectively, to give 1:1 alternating copolymers 9-10 in high yields. Cross-linked polymers 5-6 showed a thermal stability up to 300 degrees C, and showed a double phase degradation pattern in their TGA thermograms. Polymers 5-6 showed broad endothermic bands around 75-110 degrees C without any characteristic T-g peaks in DSC thermograms. Alternating copolymers 9-10, except copolymer 9b were soluble in common organic solvents. The inherent viscosities of polymer 9-10 were in the range of 0.35-0.62 dL/g. Polymer films cast from acetone solution were cloudy and tough and Tg values obtained from DSC thermograms were in the range of 118-165 degrees C.
Keywords: RING-OPENING POLYMERIZATION; ALTERNATING CO-POLYMERS; ETHYL ALPHA-CYANOCINNAMATE; COPOLYMERIZATION; ESTERS; ACETATE